2018
DOI: 10.1007/s12028-018-0588-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Feasibility, and Efficiency of a New Cooling Device Using Intravenous Cold Infusions for Fever Control

Abstract: Target temperature management with the new automated infusion device is feasible. Although we provided first data regarding safety, further controlled randomized studies are needed to evaluate the long-time safety, as well as the best indications and timing for this cooling device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A retrospective study of 52 cardiac arrest survivors found that infusion of 3800 -275 mL iced saline over about 4 hours brought core temperature from 35.3 -0.2 to 33°C, however, weights were not recorded ( Jacobshagen et al, 2009). A study examining fever control via cold saline infusion in 12 patients with acute brain injury found the mean fluid volume needed to reduce core temperature by 1°C at near-physiological temperature was 18.7 mL/kg (Willms et al, 2019). A study of nine volunteers under general anesthesia found that a 30-minute 40 mL/kg infusion of 4°C saline cooled the subjects by 2.5 -0.4°C (Rajek et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 52 cardiac arrest survivors found that infusion of 3800 -275 mL iced saline over about 4 hours brought core temperature from 35.3 -0.2 to 33°C, however, weights were not recorded ( Jacobshagen et al, 2009). A study examining fever control via cold saline infusion in 12 patients with acute brain injury found the mean fluid volume needed to reduce core temperature by 1°C at near-physiological temperature was 18.7 mL/kg (Willms et al, 2019). A study of nine volunteers under general anesthesia found that a 30-minute 40 mL/kg infusion of 4°C saline cooled the subjects by 2.5 -0.4°C (Rajek et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still concerning regarding a possible delay in the door-to-balloon time (DTB) associated with the implementation of the ETH protocol. Therefore, with the more powerful ETH systems [16], the role of cooling as an adjuvant therapy to endovascular cooling in STEMI remains unclear, but delays in ETH certainly would impair the adequate treatment of the patients.…”
Section: Introductionmentioning
confidence: 99%